2016
DOI: 10.1177/0743558416684948
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Safe in a Dangerous Place: Exploring the Neighborhood Safety Perceptions of Low-Income African American Youth

Abstract: Research shows that neighborhood safety is strongly associated with the health and well-being of adolescents. However, few studies examine what shapes these perceptions of safety, especially for adolescents who grow up in more dangerous neighborhoods. The present study explores what factors shape the neighborhood safety perceptions of a sample of low-income, African American adolescents aged 15 to 19 years ( n = 46) from Baltimore who lived in public housing as children. The study reveals the complexity in how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
3
28
0
2
Order By: Relevance
“…One of the most prominent themes that emerged from our data is that safe and dangerous spaces are embedded or overlapping, delineated by sociocontextual cues and the temporal organization of neighborhood activity. This finding upholds and extends why previous research has found that youth perceive both safety and danger in their neighborhoods (Teitelman et al, 2010;Zuberi, 2018) as well as positive and negative features (Witherspoon & Hughes, 2014). The importance of temporal organization of neighborhood space and activity has been observed in exemplar ethnographic research (e.g., Anderson, 1999;Burton & Prince-Spatlen, 1999) and supports the position that perceptions of safety and danger are intersubjectively constructed by the norms, rules, and codes of neighborhood life.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…One of the most prominent themes that emerged from our data is that safe and dangerous spaces are embedded or overlapping, delineated by sociocontextual cues and the temporal organization of neighborhood activity. This finding upholds and extends why previous research has found that youth perceive both safety and danger in their neighborhoods (Teitelman et al, 2010;Zuberi, 2018) as well as positive and negative features (Witherspoon & Hughes, 2014). The importance of temporal organization of neighborhood space and activity has been observed in exemplar ethnographic research (e.g., Anderson, 1999;Burton & Prince-Spatlen, 1999) and supports the position that perceptions of safety and danger are intersubjectively constructed by the norms, rules, and codes of neighborhood life.…”
Section: Discussionsupporting
confidence: 87%
“…Cobbina et al (2008) found that girls were more likely to avoid being outside at night, whereas boys were more likely to carry weapons, and both groups were not likely to travel alone. Other research has found that avoidance is common across both genders (Zuberi, 2018), particularly avoiding being outside at night (Stodolska et al, 2013). In a sample of young adult Black males, Smith and Patton (2016) found high rates of hypervigilance, such as constantly being "on point" (p. 215).…”
Section: Safety Strategies and Resiliencementioning
confidence: 97%
See 3 more Smart Citations